CERPEN “ISTANA TEMBOK BOLONG” KARYA SENO GUMIRA AJIDARMA: TINJAUAN POSMODERNISME - Riqko Nur Ardi Windayanto (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2022)
This study aims to reveal historical facts, irony, and parody, the opposition between the center and the periphery, and contextualization of the short story